Exploring the Health Narratives of Chinese Female Migrant Workers through Culture-Centered and Gender Perspectives. Issue 2 (28th January 2021) - Cao, Ang; Wang, Meiyun
ABSTRACT: Female migrant workers (FMWs) represent a marginalized group in China who not only face health disparities but also lack a voice in society. Drawing on the culture-centered approach (CCA) and gender perspective to co-construct health meanings with FMWs, this research aimed to answer the question of how FMWs narrate their health and to reveal the agency of the cultural members. The in-depth interview method was applied to record the health narratives of 30 participants from October 2016 to December 2016. The results showed that FMWs' understandings of health were beset by the cultural system of gender in poverty, exploited working conditions, and discrimination in the medical context. The participants identified minimum wage and medical insurance as the key structural obstacles to healthy lives in the city. Moreover, FMWs had the agency to exercise health practices that challenge the domination of biomedicine. With gender issue threaded throughout the contextualized health narratives, the role of the gender perspective could be viewed as a "contact zone" in CCA. FMWs' agency and its interactions with structures and culture indicate the significance of engaging the voices at the margins in health communication research and praxis.